Cutting-Edge Organic Synthesis and Chemical Biology of Bioactive Molecules The Shape of Organic Synthesis to Come - Kobayashi, Yuichi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book describes cutting-edge organic syntheses of biologically active compounds, isolation of pharmaceutically promising compounds from microorganisms, drug design, and progress on chemical biology. Synthetic strategy and tactics are summarized for super-carbon chain compounds, antitumor polycycles, aryl C-glycoside, antimycins, duocarmycins, cannabinoids, and other compounds. Special chapters are devoted to synthesis and biochemistry of fatty acid metabolites, which play a central role in the initiation and resolution of inflammation. The book provides a quick survey of trending topics in organic synthesis and chemical tools for biological investigation, and furnishes ideas for future research in organic synthesis. In addition, the contents can easily be understood by young chemists, graduate students, and those who are looking for new research based on organic chemistry.
1. Microbial Fraction Library: A Screening Source for Drug Discovery -- 2. Efficient Total Synthesis of Ōmura Natural Products -- 3. Enantioselective Total Synthesis of the Antitumor Polycyclic Natural Products, FR182877 and Taxol -- 4. Synthetic Approaches on the Pluramycin-class Antibiotics -- 5. Recent Progress Toward the Total Synthesis of Duocarmaycins A and SA, Yatakemaycin, and PDE-I and -II -- 6. Structure-Activity Relationship Studies of Maitotoxin Based on Chemical Synthesis -- 7. Substitution of Allylic Picolinates with Various Copper Reagents and Synthetic Applications -- 8. Total Synthesis of Ingenol -- 9. Strategies for Synthesis of Anti-inflammatory Metabolites of Unsaturated Fatty Acids -- 10. Biosynthesis, biological functions, and receptors of leukotriene B4 and 12(S)-hydroxyheptadecatrienoic acid -- 11. Synthesis of classical/non-classical hybrid cannabinoids and related compounds -- 12. Exploring bioactive marine natural products and identification of their molecular targets -- 13. Target protein chemical modification -- 14. Target Identification of Bioactive Compounds by Photoaffinity Labeling Using Diazido Probes.
Keywords: Chemistry, Organic; Medicinal chemistry; Pharmacy; Organic Chemistry; Medicinal Chemistry; Pharmacy